1986
DOI: 10.1203/00006450-198607000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Functional Residual Capacity in Normal Neonates and Children up to 5 Years of Age Determined by a N2 Washout Method

Abstract: ABSTRACT. Functional residual capacity (FRC) was determined in 50 infantsMore recently the He-dilution method has been scaled down and perfected for the use in infants (2) and the classical N2 washout technique has been computerized to allow breath by breath analysis of NZ washed out (3, 4). We have developed a simpler, open circuit N2 washout technique suitable to measure FRC in small animals and neonates (5).FRC or TGV measurements have been reported most frequently in term neonates or infants with respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 12 publications
3
27
0
1
Order By: Relevance
“…The FRC in children correlates well with height, weight, and age; but there is no difference in FRC between the sexes.4-6 The ratio of FRC to body weight increases with age. [4][5][6] reported that the ratio of FRC to body weight was 17 5:4 ml-kg -I in infants and 24 + 6 ml-kg -I in children more than one year of age. Oxygen consumption is relatively greater in younger than in older children.…”
Section: Discussionmentioning
confidence: 99%
“…The FRC in children correlates well with height, weight, and age; but there is no difference in FRC between the sexes.4-6 The ratio of FRC to body weight increases with age. [4][5][6] reported that the ratio of FRC to body weight was 17 5:4 ml-kg -I in infants and 24 + 6 ml-kg -I in children more than one year of age. Oxygen consumption is relatively greater in younger than in older children.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the disproportionate growth pattern often observed among preterm babies during early life needs to be considered when relating FRC to weight or length. 58,78 …”
Section: Expression Of Resultsmentioning
confidence: 99%
“…There is a particular controversy concerning the N 2 washout technique, because the reported values of FRC obtained using this method in healthy infants, whilst similar to helium dilution values in infants and older children [17,40,57], are considerably lower than reported with body plethysmography in infants. Measurements in normal spontaneously breathing newborn infants show that FRC measured by body-box (32-38 mL·kg -1 ) is significantly higher than the FRC measured by N 2 washout (16-19 mL·kg -1 with a regression to weight of 20.0 mL·kg -1 ) [53]. The differences may be due to several factors, such as: trapped gas not measured by the gas dilution techniques; unreliability of the plethysmographic methods in small infants because of airway closure; and technical difficulties with both the gas dilution methods.…”
Section: Equipment and Technical Proceduresmentioning
confidence: 99%
“…However, unlike the original descriptions for adults, where a 7 min period of O 2 breathing was calculated to wash out 220 mL of tissue nitrogen (up to 10% of the FRC) [24,25], it has been suggested in newborn infants that the volume of tissue and blood N 2 washed out in a test is not more than 1% of the total [40]. That is, no significant amount of N 2 is washed out during a test which ends within 2-3 min at most, and at most will cause a 5% error [39,53]. 9.…”
Section: Assumptions and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation